Valproic acid modulates radiation-enhanced matrix metalloproteinase activity and invasion of breast cancer cells. (2nd December 2015) - Artacho-Cordón, Francisco; Ríos-Arrabal, Sandra; Olivares-Urbano, María Auxiliadora; Storch, Katja; Dickreuter, Ellen; Muñoz-Gámez, José Antonio; León, Josefa; Calvente, Irene; Torné, Pablo; Salinas, María del Mar; Cordes, Nils; Núñez, María Isabel
Abstract: Purpose : To evaluate matrix metalloproteinase (MMP) activity and invasion after ionizing radiation (IR) exposure and to determine whether MMP could be epigenetically modulated by histone deacetylase (HDAC) inhibition. Material and methods : Two human breast cancer cell lines (MDA-MB-231 and MCF-7) were cultured in monolayer (2D) and in laminin-rich extracellular matrix (3D). Invasion capability, collagenolytic and gelatinolytic activity, MMP and TIMP protein and mRNA expression and clonogenic survival were analyzed after IR exposure, with and without a HDAC inhibition treatment [1.5 mM valproic acid (VA) or 1 μ M trichostatin-A (TSA)]. Results : IR exposure resulted in cell line-dependent stimulation of invasion capacity. In contrast to MCF-7 cells, irradiated MDA-MB-231 showed significantly enhanced mRNA expression of mmp-1, mmp-3 and mmp-13 and of their regulators timp-1 and timp-2 relative to unirradiated controls. This translated into increased collagenolytic and gelatinolytic activity and could be reduced after valproic acid (VA) treatment. Additionally, VA also mitigated IR-enhanced mmp and timp mRNA expression as well as IR-increased invasion capability. Finally, our data confirm the radiosensitizing effect of VA. Conclusion : These results suggest that IR cell line-dependently induces upregulation of MMP mRNA expression, which appears to be mechanistically linked to a higher invasion capability that is modifiable by HDAC inhibition.